Analysis of world strains of Anaplasma marginale using major surface protein 1a repeat sequences - de la Fuente, José (2007)
Anaplasma marginale is a tick-borne pathogen of cattle that causes the disease bovine anaplasmosis worldwide. Major surface proteins (MSPs) are involved in host-pathogen and tick-pathogen interactions and have been used as markers for the genetic characterization of A. marginale strains and phylogenetic studies. MSP1a is involved in the adhesion and transmission of A. marginale by ticks and varies among geographic strains in the number and sequence of amino-terminal tandem repeats. The aim of this study was to characterize the genetic diversity of A. marginale strains collected from countries in North and South America, Europe, Asia, Africa and Australia, inclusive of all continents. In this study, we characterized 131 strains of A. marginale using 79 MSP1a repeat sequences. These results corroborated the genetic heterogeneity of A. marginale strains in endemic regions worldwide. The phylogenetic analyses of MSP1a repeat sequences did not result in clusters according to the geographic origin of A. marginale strains but provided phylogeographic information. Seventy-eight percent of the MSP1a repeat sequences were present in strains from a single geographic region. Strong (≥80%) support was found for clusters containing sequences from Italian, Spanish, Chinese, Argentinean and South American strains. The phylogenetic analyses of MSP1a repeat sequences suggested tick-pathogen co-evolution and provided evidence of multiple introductions of A. marginale strains from various geographic locations worldwide. These results contribute to the understanding of the genetic diversity and evolution of A. marginale and tick-pathogen interactions.